Benzothienopyrimidine as a co-planar type rigid acceptor for high external quantum efficiency in thermally activated delayed fluorescence emitters. Issue 25 (3rd June 2019) - Oh, Chan Seok; Lee, Ha Lim; Hong, Wan Pyo; Lee, Jun Yeob
Abstract : Thermally activated delayed fluorescence (TADF) emitters based on a new benzothienopyrimidine acceptor, which is rigid and can form a co-planar structure via hydrogen bonding, were developed as high-efficiency TADF emitters. Abstract : Thermally activated delayed fluorescence (TADF) emitters based on a new benzothienopyrimidine acceptor, which is rigid and can form a co-planar structure via hydrogen bonding, were developed as high-efficiency TADF emitters. The benzothienopyrimidine moiety was included as an acceptor in the donor–acceptor structure which has dimethylacridine as a donor. It was demonstrated that the benzothienopyrimidine is effective as a high triplet energy acceptor unit of sky blue and greenish blue TADF emitters for efficient reverse intersystem crossing and high efficiency due to the rigidity of the acceptor unit itself and the hydrogen bonding induced co-planar structure. Two TADF emitters were derived using the benzothienopyrimidine acceptor unit and they realized high external quantum efficiency of 27.6% in greenish blue TADF organic light-emitting diodes.